Implementasi Projek Penguatan Profil Pelajar Pancasila Dalam Meningkatkan Karakter Peserta Didik Di SMA Negeri 10 Depok - Rara Aprilia Hadi Astuti; Heri Kurnia (Academy of Education Journal, 2026)
This study aims to describe the Implementation of the Pancasila Student Profile Strengthening Project in Improving Student Character at SMA Negeri 10 Depok. P5 is one of the programs presented in the independent curriculum to shape students to have competencies, values, and characters, in accordance with the Pancasila student profile, namely faith and devotion to God Almighty, global diversity, mutual cooperation, independence, critical reasoning, and creativity. The purpose of this study describes the implementation of the Pancasila student profile strengthening project in improving student character at SMA Negeri 10 Depok and to find out what challenges and obstacles teachers face in shaping student character. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews and documentation carried out from July to September. The results of this study indicate that the implementation of P5 at SMA Negeri 10 Depok through various thematic projects that are relevant to the real lives of students, such as entrepreneurship projects, environmental awareness, and strengthening national values. Through these activities, students' character development has been demonstrated, particularly in areas of responsibility, cooperation, discipline, and social awareness. However, several challenges remain in implementation, such as time constraints, differences in motivation among students, and varying student personalities.